Hydrogeology of a northern Portugal thermal area - Termas de Eirogo - Ferreira, Nuno Miguel (2019)
Sustainable exploitation of Eirogo thermal baths, located close to the city of Barcelos (Portugal) is of great interest for the region. Its exploitation is currently suspended but there are plans to resume it and reconstruct the facilities, which has motivated a preliminary hydrogeological and geochemical study of the thermal area. The study area is dominated by granitic rocks intruded in metasedimentary rocks. There are quaternary deposits and a regolith layer of a few meter thickness, through which the infiltrated water circulates and discharges to streams after a short flow path. Groundwater flow occurs only through fractures and faults at higher depths following medium- and long-term flow paths. The preferential recharge area of the Eirogo thermal water is in the NE of the watershed at an altitude of about 300 m. Water mainly flows through a large fault, having NE-SW orientation, that crosses the watershed and passes close to the thermal area. It reaches depths of around 1300 m and, afterward, comes back to the surface through a highly fractured area in which the current thermal water catchment is located. Eirogo thermal water chemical properties, especially the presence of sulfur, turns it ideal to be used in the treatment of respiratory diseases, muscle-esqueletic diseases, skin diseases, and even gynecologic diseases.